Phytochemical characterization and antibacterial evaluation of crude saps from medicinal plants in Palestinian cuisine - Sawalha , Hazem; Khasib, Said; Mansour, Bayan; Awwad, Yousef; Abu Arra, Zain; Kmail, Abdalsalam O. (Hasanuddin University Food Science and Technology Study Program, 2024)
The emergence and evolution of antibiotic-resistant bacterial strains has shifted interest in herbal therapy. Plants have long been a source of anti-infective compounds. This study investigated the antibacterial activity and phytochemical composition of various Palestinian plants against five human pathogenic bacteria. Antibacterial activity was determined using the Agar Diffusion Method (ADM), as well as the Minimal Inhibitory Concentration (MIC) and Broth Microdilution (BMD) assays. The successful ADM bacterial inhibition zones employing plant extracts were Eucalyptus camaldulensis Dehn. (E. camaldulensis) 9.35 mm, Allium sativum L. (A. sativum) 8.35 mm, Ceratonia siliqua L. (C. siliqua) 7.85 mm, and Amygdalus communis L. (A. communis) 7.85 mm. The MIC50 values against the tested microorganisms varied from 5.69 to 398.5 mg/mL. Furthermore, the MIC50 values for Gram-positive bacteria varied from 5.69 to 233.88 mg/mL, whereas the values for Gram-negative bacteria ranged from 28.65 to 398.5 mg/mL. Most species of bacteria were effectively inhibited by E. camaldulensis and A. sativum extracts. For Gram-positive and Gram-negative bacteria, the MIC50 values for E. camaldulensis were 39.01-40.38 and 31.60-85.37 mg/mL, respectively. The MIC50 values for A. sativum against Gram-positive and Gram-negative bacteria were 5.69-14.85 mg/mL and 38.98-200.11 mg/mL, respectively. The phytochemicals such as flavonoids, steroids, proteins, carbohydrates, and alkaloids in varying amounts, may explain their diverse capability to inhibit bacteria. The present study showed that E. camaldulensis, A. sativum, C. siliqua and A. communis are valuable Palestinian medicinal plants that contain antibacterial agents against the tested bacterial species. However, this study serves as a foundation for further pharmaceutical studies.